Melatonin is associated with reverse remodeling after cardiac resynchronization therapy in patients with heart failure and ventricular dyssynchrony. (15th October 2016) - Dominguez-Rodriguez, Alberto; Abreu-Gonzalez, Pedro; Piccolo, Raffaele; Galasso, Gennaro; Reiter, R.J.
Abstract: Background: Cardiac resynchronization therapy (CRT) is an effective treatment for left ventricular reverse remodeling (LVRR) in patients with congestive heart failure (HF) and ventricular dyssynchrony. Melatonin is a secretory product of the pineal gland with highly beneficial effects from any tissues including the heart. Herein, we investigated whether the response to CRT is associated with levels of melatonin before CRT implantation in patients with HF and ventricular dyssynchrony. Methods: Diurnal melatonin levels were performed in serum from 93 patients with HF and ventricular dyssynchrony before CRT implantation. Moreover, we calculated the MADIT-CRT score. Evaluation of patients at 1-year follow-up included an echocardiographic study since the patients were categorized as responders if they presented both a reduction in left ventricular end-systolic volume index > 10% and an increase in left ventricular ejection fraction > 10%. Results: At 1-year, 34 patients (36.5%) were considered responders to CRT according to the predefined criteria. The diurnal melatonin levels were significantly lower in the non-responder group (9.9 ± 2.84 vs 14.7 ± 2.32 pg/mL). After adjustment by multivariate analysis, diurnal serum melatonin levels ( P  < 0.001) and diabetes mellitus ( P  = 0.03) were predictors of LVRR. On Cox regression analysis, diurnal serum melatonin levels ( P   <  0.001) and left atrial volume < 40 mL/m 2 ( P  = 0.04) remained independent predictors of the adverse clinical events. The area under of curve for the prediction LVRR of melatonin (0.91, 95%CI 0.85–0.97; P  < 0.001) was significantly higher compared to MADIT-CRT score (0.69, 95%CI 0.58–0.80; P  = 0.002). Conclusion: Diurnal levels of melatonin before CRT implantation are associated with LVRR at 12 month follow-up.